Unusual Site for a White Nodule on the Palatine Tonsil: Presentation, Differential Diagnosis, and Discussion - Ashwag Yagoub Aloyouny (Case Reports in Dentistry)
Introduction. Palatine tonsils are part of the mucosa-associated lymphoid tissue, located in the oropharyngeal region. Although these tissues protect the body from foreign intruders, they are more prone to infections due to their anatomical structure and location. For instance, the differential diagnosis of a white lesion on the palatine tonsil can range from benign to malignant lesions. Oral lymphoepithelial cysts commonly arise as painless, yellowish nodules on the floor of the mouth and the ventral or lateral surface of the tongue. Case Presentation. This paper presents a rare case of an unusual site of a lymphoepithelial cyst (LEC) in the oral cavity. The lesion was located in the tonsil of a 20-year-old woman with a chief complaint of a painless, white lump in the back of the mouth for nine months. Discussion. The differential diagnosis of a white lesion on the palatine tonsil is caused by several factors, such as bacterial, viral, and fungal infections; trauma; stones; cysts; abscess; or cancer. In this case, both the clinical presentation and extra- and intraoral examinations were highly associated with LEC. Oral LEC etiopathogenesis is uncertain, and several theories have been proposed to discuss the causes of LEC. In addition, oral LEC could be monitored without surgical intervention if the nodule is asymptomatic. Conclusion. We emphasize the importance of a thorough clinical examination of oral and oropharyngeal lesions, which are usually neglected.